What do we know about the future of food systems in India? - Balaji, Sedithippa Janarthanan; Birthal, Pratap S.; Pal, Barun Deb (International Food Policy Research Institute, 2025)
Rapid growth in the livestock and fisheries subsectors, driven by increasing demand, has advanced the frontiers of agricultural growth in India.